Integrating non-coding RNA profiling with HPV genotyping for cervical cancer risk stratification and early detection - Priyanshi Singh; Brij Bhushan; Anoop Kumar; Gauri Misra; Neelima Mishra (Molecular Biology Reports, 2026)

Spatiotemporal assessment and machine learning-based prediction of PM2.5 Emissions from biomass combustion in Rural India - Pradeep Kumar; Era Upadhyay; Anoop Yadav (Bulletin of Atmospheric Science and Technology, 2026)

Hydrocarbons and genomic biomarker-based paleoclimate and ecological variability over the past 15 kyr from Toli Lake, Garhwal Himalaya - Sushmita Singh; Vishakha Bisht; Ambili Anoop; Shravi Agarwal; Pankaj Kumar; A.S. Maurya; Naveen K. Navani; A.P. Dimri; Pradeep Srivastava (Quaternary Science Reviews, 2026)

Linking urban greening systems with SDG 11 and SDG 13: A systematic literature review (2014–2024) for climate-resilient and sustainable cities - Shenoy B. Gowri; Anoop Kumar Shukla (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Pteropod vulnerability to ocean acidification in the eastern Arabian Sea - Mayuri Raut; Suhas S. Shetye; Biraja Kumar Sahu; Ajay Kumar Jena; Anoop Babu; Sarvesh Vaigankar (Estuarine, Coastal and Shelf Science, 2026)

Green synthesis of ZnO nanoparticles from the leaves of Passiflora foetida L. and its antimicrobial and cytotoxic activities - Kushankur Sarkar; Sangita Dey; Ayan Kumar Mahanty; Anoop Kumar; Chandrani Choudhuri; Monoranjan Chowdhury (The Science of Nature, 2026)

Shatavarin IV from Asparagus curillus roots exhibits antidiabetic activity in STZ-induced rats - Anoop Singh Negi; Veerma Ram; Ankit Kumar; Ankush Sundriyal; Ruchi Badoni Semwal; Deepak Kumar Semwal (Natural Product Research, 2026)

Modern catchment soil–lake sediment linkages: Proxy distribution patterns in a small lake in coastal Karnataka, southern India - A.S. Yamuna; Anish Kumar Warrier; Jyoti Srivastava; Anoop Ambili; Firoz Badesab; Mamilla Venkateshwarlu; K. Sandeep; Pranav Prakash; Soumyashree Behera; G.S. Joju; Diptimayee Behera (Quaternary International, 2026)

Long-term changes in winter fog over Delhi, India: A 20-year climatology based on airport observations and urban expansion - Anoop Kumar Mishra; Srabanti Ballav; Mohammd Rafiq (Theoretical and Applied Climatology, 2026)

Three Decades of Winter Fog Variability at Delhi IGI Airport: Trends, Persistence, and Environmental Drivers Using Sen’s Slope and Transition Probability Analysis - Srabanti Ballav; Anoop Kumar Mishra; Gajendra Kumar; Sourav Adhikary (Pure and Applied Geophysics, 2026)

Unraveling the short-duration Delhi dust storm: insights from In-Situ, satellite, and reanalysis datasets - Krishna Kumar Shukla; Sukhwinder Kaur; Gajendra Kumar; Kondapalli Niranjan Kumar; Anoop Kumar Mishra; Raju Attada; Brajesh Kumar Kanaujiya (Air Quality, Atmosphere & Health, 2026)

Revealing DNA damage levels in rat testicular germ cells in vivo using an adapted version of the alkaline comet assay - Ann-Karin Hardie Olsen; Xiaoxiong Ma; Congying Zheng; Yvette Dirven; Dag Markus Eide; Gunnar Brunborg; Anoop Kumar Sharma (Archives of Toxicology, 2026)

Chemical weathering induced carbon sink potential of a highly populated tropical biodiversity hotspot: Evidences from Riverine pCO2 and δ13CDIC - Kiran Kumar Reddy; Upendra Badimela; Harish Gupta; Shive Prakash Rai; Anoop Krishnan Krishnan; T.M. Vishnu Maya; D.V. Reddy; Devender Kumar (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Hydrogeochemical characterization, spatial distribution, and suitability of groundwater for drinking and irrigation in the Aravalli Range, Haryana, India - Manoj Kumar; Anoop Yadav; Manjeet Bansal; Vinod Kumar Garg; Pawan Kumar Rose; Ram Pravesh Kumar; Bhupendra P. Singh (Environmental Sustainability, 2026)

Quality-by-design-based fabrication of betaxolol hydrochloride-loaded nano-ocular carrier via ternary phase mapping of solid/liquid lipids and BBD modeling for enhanced transcorneal flux and IOP-lowering effect - Nishant Kumar; Anoop Kumar; Sokindra Kumar (AAPS PharmSciTech, 2026)

Atmospheric drivers of the 26 May 2025 heavy rainfall event over mumbai: insights from observations and reanalysis - Krishna Kumar Shukla; Anoop Kumar Mishra; Gajendra Kumar; Dipak Kumar Sahu; Shubhangi Bhute; Sourav Adhikary (Natural Hazards, 2026)

State-wide assessment of mangrove blue carbon stocks in coastal Karnataka, South-west coast of India - Darwin Ramteke; Ajay Kumar; Anoop Babu; Suhas Suresh Shetye; H.S. Suresh; Cathrine Sumathi Manohar (Journal of Environmental Management, 2026)

Engineered self-sterilizing face masks via silver nanowire-microparticle composite ink printed on fabrics - Adarsh Sivan Pillai; Harris Varghese; Velayudhanpillai Prasannakumari Adarsh; Anoop Puthiyamadam; Sumith Sudhakar; Rajeev Kumar Sukumaran; Achu Chandran; Surendran Kuzhichalil Peethambharan (Chemical Engineering Journal, 2026)

Optimizing Nitrogen Fertilization in Oat Using the Chlorophyll Meter: Threshold Determination for Yield, Fodder Quality and Nitrogen Use Efficiency - Mukesh Choudhary; Prabhu Govindasamy; Anoop Kumar Dixit; Sita Ram Kantwa; Asha Ram; Dana Ram Palsaniya; Sunil Kumar (Journal of Soil Science and Plant Nutrition, 2026)

Spatio-temporal analysis of rainfall extremes and drought variability in the Tel basin, Odisha, India, under changing climate - Pushpanjali Kumari; H. P. Singh; Pankaj Dangi; Anoop Kumar Shukla (Innovative Infrastructure Solutions, 2026)
Climate change has significantly influenced temperature and rainfall patterns, disrupting hydrological cycles and increasing extreme weather events. This study analyses spatial and temporal variations in rainfall trends and extreme climatic indices in the Tel Basin, Odisha, India, from 1981 to 2021. Rainfall trends were assessed using the Mann–Kendall test and Sen’s slope estimator, while extreme climatic indices were evaluated using the Climpact tool. Drought variability was examined using the Standardized Precipitation Index (SPI) and the Standardized Precipitation Evapotranspiration Index (SPEI), accounting for the role of temperature in drought intensification. The results reveal pronounced spatial heterogeneity in rainfall trends. Monsoon rainfall shows increasing trends (up to 17.48 mm/decade), while pre-monsoon rainfall is declining (up to −2.64 mm/decade). Heavy rainfall events (R20mm, R30mm) are rising, whereas consecutive dry days (CDD) have increased by ~ 5 days/decade and consecutive wet days (CWD) have decreased by ~ 3 days/decade. Drought analysis shows that SPI-6 exhibits a weak increasing trend (Sen’s slope = 0.001), whereas SPEI-6 indicates a stronger drying pattern (Sen’s slope = − 0.005), highlighting the influence of rising temperatures. Temperature extremes, such as TXx (~ 0.02 °C year⁻ 1 ), along with an increase in tropical nights, indicate intensified warming, which enhances evapotranspiration and increases agricultural water stress. The results stress the urgent need for adaptive water resource management, climate-resilient agriculture, and improved irrigation planning in the Tel Basin to combat the growing climate-induced vulnerabilities.

Indoor 3D geometry estimation using single panorama image - Surendra Kumar Sharma; Kamal Jain; Anoop Kumar Shukla (Applied Geomatics, 2026)

Investigating the planform dynamics and LULC changes with predictive insights in a Sub-Himalayan Transboundary River Basin, India - Jiarul Alam; Deepak Kumar Mandal; Jahurul Mandal; Harekrishna Manna; Sanjoy Barman; Anoop Kumar Shukla (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Assessment and Monitoring of Hydrological and Groundwater Quality In and Around Sugar Factory: A comprehensive Study - Divya Patel; Ananthalakshmi Ranganathan; Seema Paroha; Anoop Kumar Kanaujia (Sugar Tech, 2026)

Identification of novel signal of DRESS associated with antibiotics: a disproportionality analysis of the FDA adverse event reporting system (FAERS) database - Khushi Goyal; Ruchika Sharma; Ashok Kumar Datusalia; Gopal L. Khatik; Anoop Kumar (European Journal of Clinical Pharmacology, 2026)

Molecular docking, dynamics and experimental approach integrated identification of phytopharmaceuticals against methicillin-resistant Staphylococcus aureus (MRSA) infection - Saima; Hitesh K Sharma; S. Latha; Viney Lather; Devesh Tewari; Ruchika Sharma; Gaurav Kumar Jain; Deepti Pandita; Anoop Kumar (Folia Microbiologica, 2026)

Characteristic dissimilarities in the cloud base height over Indo-Gangetic plain airports during withdrawal phase of southwest monsoon - Krishna Kumar Shukla; Gajendra Kumar; Anoop Kumar Mishra; Sourav Adhikary; Neeti Singh; Manish R. Ranalkar; Radheshyam Sharma; Manish Rai; Anand Shankar (Meteorology and Atmospheric Physics, 2026)

Assessing persistent heavy rainfall-triggered landslides in southern India in July 2024 through space-based observations - Anoop Kumar Mishra; Mohammad Suhail Meer; Nagaraju Vanganuru; Gajendra Kumar; Sourav Adhikary; Krishna Kumar Shukla (Advances in Space Research, 2026)

Wind direction dominates the transport and deposition of fire proxies in tropical dry forest landscapes of the Western Ghats - Prabhakaran Ramya Bala; Kumar Nithin; Diptimayee Behera; Ambili Anoop; Binisia Sanatan; Velu Vinoj; Raman Sukumar (Global and Planetary Change, 2025)

Occurrence, sources, and controlling factors of emerging organic pollutants in a freshwater lake system in the NW Himalayas - Sunil Kumar; Mehta Bulbul; Diptimayee Behera; Arshid Jehangir; Ambili Anoop (Environmental Nanotechnology, Monitoring & Management, 2025)

Integrated trend analysis and meteorological drought forecasting using ANN in the adjacent semi-arid and arid regions - Uttam Singh; Anoop Kumar Mishra; Mahender Choudhary (Theoretical and Applied Climatology, 2025)

Exploring the Synergistic Effect of Thymol with Oxacillin against Methicillin Resistant Staphylococcus aureus - Hitesh K. Sharma; Amarnath Karna; Sajendra K. Verma; Puneet Gupta; Dheeraj Nagpal; Anoop Kumar; Deepti Pandita; Monalisa Mukherjee; Virinder S. Parmar; Pallavi Agarwal; Viney Lather (Indian Journal of Microbiology, 2025)

Microplastic contamination in environmental matrices of multi-basin Dal Lake, Kashmir - Aarif Yaseen; Soha ul Islam; Kumar Ajay; Sami Ullah Bhat; Arshid Jehangir; Anoop Ambili (Science of The Total Environment, 2025)

Drought risk and hydrological changes in the Ganga River Basin, India - Chetan Sharma; Deen Dayal; Anoop Kumar Shukla (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Comparative nutritional profiling of underutilized millets for sustainable use in current food system - Saroj Kumar; Arpit Chauhan; Piyush Verma; Anoop Shakya; Prasant Kumar Rout; Manisha Prasad; Chandra Sekhar Mohanty (Journal of Cereal Science, 2025)

On the Variability of Cumulonimbus Clouds over Indo-Gangetic Plain Region and Their Thermodynamical Linkage - Krishna Kumar Shukla; Anoop Kumar Mishra; Gajendra Kumar (Journal of the Indian Society of Remote Sensing, 2025)

Drainage basin analysis of Sunai River, Odisha, India: A remote sensing and GIS-based approach - Pawan Kumar Gautam; Dhirendra Kumar; Satyajit Sahu; Anoop Kumar Singh (Arabian Journal of Geosciences, 2025)

Preliminary analysis and applications of the Indian Ocean wave drifter program - P. G. Remya; N. Suresh Kumar; Sundhar B. Mithun; B. Praveen Kumar; T. R. Anoop; Venkat Shesu Reddem; C. Jeyakumar; Aneesh A. Lotliker; E. Pattabhi Rama Rao; T. M. Balakrishnan Nair (Frontiers in Marine Science, 2025)
The Southern Ocean (SO) is a critical driver of global wave dynamics, generating long-period swells that propagate vast distances and significantly impact far distant coastal regions, including the Indian coastal regions. Climate change has intensified westerly winds and altered storm tracks in the Southern Hemisphere, resulting in higher wave heights and longer periods, which in turn increase the risk to coastal regions.​ However, the remote and harsh environment in the SO has historically limited in-situ wave observations, hindering a comprehensive understanding of the wave characteristics in the region. To bridge this gap, the Indian National Centre for Ocean Information Services (INCOIS) launched the Indian Ocean Wave Drifter (IOWD) program in 2021 under the Deep Ocean Mission to address the in-situ data gap in the Southern Indian Ocean. Through the deployment of GPS-enabled directional wave spectra drifters, the program has enabled near-real-time observations of wave characteristics across the SO. This article highlights the early outcomes of the IOWD program, including wave model validation, Stokes drift estimation, and swell tracking. The study emphasizes the importance of sustained in-situ observations from remote oceans for improving wave forecasting, enhancing coastal preparedness, and advancing scientific understanding of wave–current interactions and climate variability in the Indian Ocean region.

Biochemical profiling, anti-biofilm, and anti-quorum sensing activities of Psophocarpus tetragonolobus (L.) DC. root-tuber - Rayees Ahmad Lone; Umesh Chandra Sahoo; Anoop Shakya; Nem Kumar Ngpoore; Nasreen Bano; Rojalin Pattanayak; Brahma N. Singh; Chandra Sekhar Mohanty (Natural Product Research, 2025)

Development and Performance Evaluation of Tractor-Operated Sugarcane Single Bud Sett Cutter Planter for Resource Conservation - Omprabha; Sukhbir Singh; Anoop Kumar Dave (Sugar Tech, 2025)

Design and Development of Butyrosomes as Novel Carriers Using Lipid Isolated from Diploknema butyracea (Roxb.) H. J. Lam - Abhishek Anand; Jyoti Saini; Nitish Singh Jangwan; Gaurav Kumar Jain; Anoop Kumar; Surajpal Verma; Devesh Tewari (Journal of Pharmaceutical Innovation, 2025)

Youngest Toba Tuff (YTT) beds as a Late Pleistocene isochron in the Indian subcontinent? New geochronological and sedimentological insights - Devara Anil; Monika Devi; Prabhin Sukumaran; B. V. Lakshmi; K. Deenadayalan; Sunil Kumar; Ambili Anoop; Zakir Khan; Vrushab Mahesh; Gopesh Jha; P. Ajithprasad; Naveen Chauhan (Journal of Quaternary Science, 2025)
The ~75 ka Young Toba super‐eruption was a catastrophic extreme event that spewed vast quantities of volcanic ash and aerosols and is argued to have caused a drastic volcanic winter, climatic upheaval, and a human genetic bottleneck. The global and regional impacts of the eruption on climate dynamics and past hominin populations are strongly contested due to conflicting global climatic records and archeological datasets. The Indian subcontinent is a key place for Toba research due to its proximity to Mt. Toba (Indonesia). Most of central and peninsular India is estimated to have been covered by a ~5 cm ash layer, with deposits found in different fluvial systems across the subcontinent. For a long time, many of these Youngest Toba Tuff (YTT) deposits, occurring in both archeological and non‐archeological contexts, were believed to be primary tephra deposits dating to ~75 ka. However, the use of YTT as a Late Pleistocene chronological marker is surrounded by many uncertainties, primarily due to the complex and varying nature of the depositional and sedimentary contexts of YTT and chronological irregularities. Recent sedimentological and geochronological data indicate that most of the YTT deposits in India are secondary deposits, resulting from later erosion and redeposition occurring thousands of years after the eruption. This highlights the unreliability of YTT as an isochron and raises questions about the credibility of paleoclimate (terrestrial and marine) and archeological datasets that use YTT as a chronological marker. Our study contributes to this debate and reveals the complex redepositional history of YTT deposits in the Indian subcontinent through geochronological and geoarchaeological analyses of YTT‐bearing sequences from Motravulapadu, Andhra Pradesh, India. Our findings suggest that the final burial of YTT occurred around 30 ka, highlighting a temporal gap of more than 40 000 years after the eruption. Notably, the redeposited tephra horizon appears visually uniform and compositionally pure, despite its secondary context, adding complexity to its stratigraphic interpretation. Our multiproxy sedimentological approach demonstrates the importance of integrating detailed stratigraphic, magnetic, granulometric, and chronological analyses to resolve such depositional ambiguities; it underscores the need for similar frameworks in future studies of YTT‐bearing sequences. We suggest that YTT in India cannot be used as a reliable chronological marker without independent age estimations of its deposition. However, it has significant potential for identifying regional geological events.

Effect of colchicine treatment and polyploidy induction on morphological, biochemical, and cytological characteristics of Lepidium sativum Linn․ - Priyanka Pandey; Girjesh Kumar; Anoop Kumar Verma (South African Journal of Botany, 2025)

Tri-terpenoids from Ficus rumphii May Arrest Carcinogenic Progression Through the Inhibition of MDM2-p53 Gene Interaction - Gargi Sen; Swarnendra Banerjee; Indrani Sarkar; Sutapa Datta; Sandipan Ghosh; Pallab Kar; Anoop Kumar; Arnab Sen (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2025)

Machine learning-guided Orbitrap-HRAMS-based metabolomic fingerprinting for geographical origin, variety and tissue specific authentication, and adulteration detection of turmeric and ashwagandha - CH. Ratnasekhar; Abhishek Kumar Rai; Poonam Rakwal; Samreen Khan; Anoop Kumar Verma; Pradipto Mukhopadhyay; Priya Rathor; Lal Hinghrani; Nicholas Birse; Ritu Trivedi; Prabodh Kumar Trivedi (Food Chemistry, 2025)

Next-gen storm nowcasting: harnessing satellite-based radar reflectivity over India - Anoop Kumar Mishra; Abhisek Chhari; Gajendra Kumar; Bipasha Paul Shukla; Randhir Singh; Pradeep Kumar Thapliyal; Sourav Adhikary; Krishna Kumar Shukla (Theoretical and Applied Climatology, 2025)

Satellite-based assessment of extreme rainfall during the 2019 Indian monsoon: climatic linkages to IOD and ENSO - Mohammad Suhail Meer; Anoop Kumar Mishra; Vanganuru Nagaraju; Jayanta Das; Aqil Tariq (Modeling Earth Systems and Environment, 2025)

Assessing physical and mental health impacts of solid cooking fuel emissions - Pradeep Kumar; Era Upadhyay; Anoop Yadav; Krishnamurthi Kannan (Air Quality, Atmosphere & Health, 2025)

Phosphorus Use Kinetics of Citrus Grafts Versus Rootstocks Alone: Morphological, Physiological, and Biochemical Responses - Amanda Veridiana Krug; Adriele Tassinari; Álvaro Luís Pasquetti Berghetti; Jean Michel Moura-Bueno; Eduardo Maciel Haitzmann dos Santos; Raíssa Schwalbert; Ana Luiza Lima Marques; Daniéle Gonçalves Papalia; Fernando Teixeira Nicoloso; Luciane Almeri Tabaldi; Anoop Kumar Srivastava; Gustavo Brunetto (Journal of Soil Science and Plant Nutrition, 2025)

Rapid metabolic fingerprinting meets machine learning models to identify authenticity and detect adulteration of essential oils with vegetable oils: Mentha and Ocimum study - CH Ratnasekhar; Samreen Khan; Abhishek Kumar Rai; Himanshu Mishra; Anoop Kumar Verma; Raj Kishore Lal; T.M. Ananda Kumar; Christopher T Elliott (Food Chemistry, 2025)

Aerosol volatility over a high-altitude site in India: Effect of semi-volatile organics - Subrata Mukherjee; Rohit D. Patil; M.Y. Aslam; G.S. Meena; V. Anil Kumar; Sachin S. Patil; Anoop S. Mahajan; Liselotte Tinel; Vinayak V. Waghamare; G. Pandithurai (Atmospheric Research, 2025)

Thunderstorm prediction over Eastern state of India during pre-monsoon season in 2018 using artificial neural network model - Nagaraju Vanganuru; P. Sardar Maran; L. Lakshmanan; Anoop Kumar Mishra; Araveti Sandeep (Theoretical and Applied Climatology, 2025)

Correction: Performance Evaluation of INSAT‑3D Derived Outgoing Long Wave Radiation Over India Using Remotely Sensed Observations - Anoop Kumar Mishra; Chander Singh Tomar; Gajendra Kumar; Ashim K. Mitra; Subhash Chander Bhan (Journal of the Indian Society of Remote Sensing, 2025)

Long-term variability of the low-level clouds across Indo-Gangetic Plain - Krishna Kumar Shukla; Gajendra Kumar; Chander Singh Tomar; Raju Attada; Kondapalli Niranjan Kumar; Anoop Kumar Mishra (Dynamics of Atmospheres and Oceans, 2025)

Nanotechnology Driven Lipid and Metalloid Based Formulations Targeting Blood–Brain Barrier (3B) for Brain Tumor - Amulya Jindal; Mainuddin; Anoop Kumar; Ratneshwar Kumar Ratnesh; Jay Singh (Indian Journal of Microbiology, 2025)

Design and analyses of an AB5 - metal hydride based canister for hydrogen compressor application - Kakumanu Suvarna Jaya Prakash; K.Kishor Kumar; Vinod Kumar Sharma; Prem Kumar Chaurasiya; Tikendra Nath Verma; Anoop Kumar Shukla; Gaurav Dwivedi (Process Safety and Environmental Protection, 2025)

Biochars improve agricultural production: The evidence base is limited - Vincent CHAPLOT; Philippe BAVEYE; René GUENON; Elie LE GUYADER; Budiman MINASNY; Anoop Kumar SRIVASTAVA (Pedosphere, 2025)

Microplastics influencing aquatic environment and human health: A review of source, determination, distribution, removal, degradation, management strategy and future perspective - Pawan Kumar; Anil Kumar; Deepak Kumar; Kalp Bhusan Prajapati; Ambrish Kumar Mahajan; Deepak Pant; Anoop Yadav; Anand Giri; Satish Manda; Soniya Bhandari; Richa Panjla (Journal of Environmental Management, 2025)

Engineering Properties of Sugarcane for the Development of Efficient Sugarcane Machinery - Omprabha; Sukhbir Singh; Anoop Kumar Dave (Sugar Tech, 2025)

Investigation of monkeypox disease transmission with vaccination effects using fractional order mathematical model under Atangana-Baleanu Caputo derivative - Jatin Bansal; Amit Kumar; Anoop Kumar; Aziz Khan; Thabet Abdeljawad (Modeling Earth Systems and Environment, 2025)

Predicting temperature variability in major Indian cities using Random Forest Regression (RFR) Model - Ashish Alone; Anoop Kumar Shukla; Gopal Nandan; D R Pattanaik (Journal of Earth System Science, 2025)

Metabolomics in Depression: What We Learn from Preclinical and Clinical Evidences - Pooja Singh; Boosani Vasundhara; Nabanita Das; Ruchika Sharma; Anoop Kumar; Ashok Kumar Datusalia (Molecular Neurobiology, 2025)

Performance Evaluation of INSAT-3D Derived Outgoing Long Wave Radiation Over India Using Remotely Sensed Observations - Anoop Kumar Mishra; Chander Singh Tomar; Gajendra Kumar; Ashim K. Mitra; Subhash Chander Bhan (Journal of the Indian Society of Remote Sensing, 2025)

Evaluation of cooking practices in India to achieve SDGs 7.1.2 - Pradeep Kumar; Era Upadhyay; Krishnamurthi Kannan; Anoop Yadav (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Exploring the utility of nonlinear hybrid optimization algorithms in seismic inversion: A comparative analysis - Ravi Kant; Brijesh Kumar; S.P. Maurya; Raghav Singh; Anoop Kumar Tiwari (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Spatio-temporal analysis of riverbank changes using remote sensing and geographic information system - S.M. Shravan Kumar; Manish Pandey; Anoop Kumar Shukla (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Atmospheric deposition of microplastics in an urban conglomerate near to the foothills of Indian Himalayas: Investigating the quantity, chemical character, possible sources and transport mechanisms - Yadav Ankit; Kumar Ajay; Sharma Nischal; Sahil Kaushal; Vishal Kataria; Elisabeth Dietze; Ambili Anoop (Environmental Pollution, 2024)

Grain size and sediment load control on channel migration patterns of the Ghaghara river from Faizabad to Deoria, Ganga plain, India - Pawan Kumar Gautam; Dhruv Sen Singh; Dhirendra Kumar; Anoop Kumar Singh (Arabian Journal of Geosciences, 2024)

Hydrogen production, storage, and CI Engine utilisation: A global perspective - Kaustubh Singh; Tikendra Nath Verma; Gaurav Dwivedi; Anoop Kumar Shukla (Process Safety and Environmental Protection, 2024)

Hormesis of black soldier fly larva: Influence and interactions in livestock manure recycling - Mukesh Kumar Awasthi; Andrei Mikhailovich Dregulo; Anoop Yadav; Vinay Kumar; Manoj Kumar Solanki; Vinod Kumar Garg; Raveendran Sindhu (Journal of Environmental Management, 2024)

Microplastics and heavy metal contamination along a land-use gradient in a Himalayan foothill river: Prevalence and controlling factors - Sunil Kumar; Diptimayee Behera; Kumar Ajay; Balasubramanian Karthick; Chetan Dharia; Ambili Anoop (Journal of Contaminant Hydrology, 2024)

3D point cloud reconstruction using panoramic images - Surendra Kumar Sharma; Kamal Jain; Anoop Kumar Shukla (Applied Geomatics, 2024)
Panorama photogrammetry, the process of analyzing panoramic images, has gained popularity in close-range photogrammetry for 3D reconstruction over the past decade. Initially, researchers utilized cylindrical or spherical panoramic images created through specialized cameras or conventional ones with rectilinear lenses. However, these methods were hindered by the high cost of panorama equipment and the need for manual reconstruction. Consequently, there's a growing demand for automated algorithms capable of reconstructing 3D point clouds from stitched panorama images. This study aims to provide a cost-effective solution for automatic 3D point cloud reconstruction from panoramas. The study is divided into two parts; it first outlines an image acquisition strategy for capturing overlapping perspective images to facilitate accurate panorama generation. Subsequently, it introduces an automated algorithm for 3D point cloud reconstruction from panorama images. The process utilizes the KAZE feature detector for feature detection and introduces a novel feature matching approach for matching panorama images. Accuracy assessment of the reconstructed 3D point clouds was done using three methods: Line Segment Based approach, yielding RMSE errors of 34.2mm and 39mm for dataset-1 and dataset-2 respectively, No-Reference 3D Point Cloud Quality Assessment, resulting in quality scores of 8.5939 and 7.4535 for dataset-1 and dataset-2 respectively, and M3C2 distance method computed value of 0.091059 and 0.165179 respectively, indicating high quality of the generated point clouds.

Comparative analysis of energy, exergy, emission, and sustainability aspects of third generation microalgae biodiesels in a diesel engine - Aman Singh Rajpoot; Tushar Choudhary; H. Chelladurai; Anoop Kumar Shukla; Abhinav Anand Sinha (Process Safety and Environmental Protection, 2024)

Green ammonia production: Process technologies and challenges - Neelam Bora; Akhilesh Kumar Singh; Priti Pal; Uttam Kumar Sahoo; Dibyakanta Seth; Dheeraj Rathore; Sudipa Bhadra; Surajbhan Sevda; Veluswamy Venkatramanan; Shiv Prasad; Anoop Singh; Rupam Kataki; et al. (Fuel, 2024)

Seasonal variability of volatile organic compounds (VOCs) at a high-altitude station in the Western Ghats, India: Influence of biogenic, anthropogenic emissions and long-range transport - Subrata Mukherjee; G. Pandithurai; Vinayak Waghmare; Anoop S. Mahajan; Liselotte Tinel; M.Y. Aslam; G.S. Meena; Sachin Patil; Pallavi Buchunde; Anil Kumar (Atmospheric Environment, 2024)

Correction to: On the Changes in Precipitation Spectrum Over India Using High-Resolution Precipitation Estimates from Remote Sensing Observations - Anoop Kumar Mishra; Ashim K. Mitra; Subhash Chander Bhan (Journal of the Indian Society of Remote Sensing, 2024)

Emerging pollutant in surface water bodies: a review on monitoring, analysis, mitigation measures and removal technologies of micro-plastics - Abdul Gani; Shray Pathak; Athar Hussain; Anoop Kumar Shukla; Sasmita Chand (Environmental Geochemistry and Health, 2024)

Advances in the targeted theragnostics of osteomyelitis caused by Staphylococcus aureus - Tahir Abdulrehman; Shahnaz Qadri; Yousef Haik; Ali Sultan; Sini Skariah; Shourya Kumar; Zachary Mendoza; Kamlesh K Yadav; Anoop Titus; Shameer Khader (Archives of Microbiology, 2024)

An approach towards different techniques for detection of heavy metal ions and their removal from waste water - Anoop Singh; Shahid Shafi Shah; Chandan Sharma; Vinay Gupta; Ashok K. Sundramoorthy; Pawan Kumar; Sandeep Arya (Journal of Environmental Chemical Engineering, 2024)

Bioinspired synthesis of silver nanoparticles using Luffa aegyptiaca seed extract and assessment of pharmacological properties - Sudipta Pradhan; Apurba Roy; Ayon Saha; Priya Das; Gouhar Jahan Ashraf; Tania Baishya; Ankrita Thapa; Tarun Kumar Dua; Paramita Paul; Gouranga Nandi; Partha Pratim Maiti; Koyeska Roy; et al. (Biocatalysis and Agricultural Biotechnology, 2024)

Feeding potential and foraging behaviour of cheilomenes sexmaculata (F.) on cotton whitefly, Bemisia tabaci (Gennadius) - Rakesh Kumar; Sachin S. Suroshe; Y. Venkanna; M. C. Keerthi; Anoop Kumar; Subhash Chander (International Journal of Tropical Insect Science, 2024)

Climate changes altered the citrus fruit quality: A 9-year case study in China - ZhiHao Dong; MengXin Chen; Anoop Kumar Srivastava; Ul Hassan Mahmood; Muhammad Ishfaq; XiaoJun Shi; YueQiang Zhang; Mohamed G. Moussa; XueXian Li; ChengXiao Hu; FuSuo Zhang (Science of The Total Environment, 2024)

Thermo-economics, emissions, and sustainability comparison of a novel hybrid evaporative cooled solid oxide fuel cell-recuperated gas turbine with conventional system - Abhinav Anand Sinha; Tushar Choudhary; Anoop Kumar Shukla; P. Ahmadi (Process Safety and Environmental Protection, 2024)

Investigation of Meteorological Characteristics of Tropical Supercyclone Shaheen Insights from High-Resolution Satellite Observations - Mohammad Suhail Meer; Anoop Kumar Mishra; Vanganuru Nagaraju (Journal of the Indian Society of Remote Sensing, 2024)

Understanding zebrafish sleep and wakefulness physiology as an experimental model for biomedical research - Rima Singh; Deepali Sharma; Anoop Kumar; Charan Singh; Arti Singh (Fish Physiology and Biochemistry, 2024)

Vegetation Index (NDVI) reconstruction from western Himalaya through dendrochronological analysis of Cedrus deodara - Anoop Kumar Singh; Santosh K. Shah; Uttam Pandey; Deeksha; Lamginsang Thomte; Tanveer W. Rahman; Nivedita Mehrotra; Dhruv Sen Singh; Bahadur Singh Kotlia (Theoretical and Applied Climatology, 2024)

On the Changes in Precipitation Spectrum Over India Using High-Resolution Precipitation Estimates from Remote Sensing Observations - Anoop Kumar Mishra; Ashim K. Mitra; Subhash Chander Bhan (Journal of the Indian Society of Remote Sensing, 2024)

Landfill leachate analysis from selected landfill sites and its impact on groundwater quality, New Delhi, India - Athar Hussain; Anandita Deshwal; Manjeeta Priyadarshi; Shray Pathak; Geetha Sambandam; Sasmita Chand; Anoop Kumar Shukla (Environment, Development and Sustainability, 2024)

Qualitative–quantitative comparative assessment of conventional gas turbine with fuel cell-based integrated power cycle - Abhinav Anand Sinha; Tushar Choudhary; Mohd. Zahid Ansari; Anoop Kumar Shukla (Environment, Development and Sustainability, 2023)

In vitro pharmacological evaluation, phytochemical profiling, and in silico molecular docking of Duabanga grandiflora leaves and flowers - Priya Das; Gouhar Jahan Ashraf; Tania Baishya; Tarun Kumar Dua; Paramita Paul; Gouranga Nandi; Ravi Kumar Singh; Ankita Dutta; Anoop Kumar; Ranabir Sahu (Vegetos, 2023)

Fluoride distribution, contamination, toxicological effects and remedial measures: a review - Anoop Yadav; Neeraj Kumari; Rajesh Kumar; Manoj Kumar; Sushma Yadav (Sustainable Water Resources Management, 2023)

Lignin Depolymerization for Its Valorization - Dixita Chettri; Shadab Ahmed; Anoop Anand Malik; Anil Kumar Verma (BioEnergy Research, 2023)

Draft whole-genome sequence of ‘Candidatus Liberibacter asiaticus’ strain AS-TNSK3 from a Khasi mandarin (Citrus reticulata) tree in Northeast India - Ashis K. Das; Prasanth Tej Kumar Jagannadham; Ruchi Bhate; Anoop K. Srivastava; Popy Bora; Madhumita Barooah (Journal of Plant Pathology, 2023)

Protective effects of indigenous lactic acid bacteria in Artemia salina challenged with Vibrio parahaemolyticus : an in vitro and in silico approach - Abigail Fernandes; Avelyno D’Costa; Akhil Nair; Santosh Jathar; Anoop Kumar Yadav; Pamela Jha; Vinothkannan Ravichandran; Renitta Jobby (Marine Biology Research, 2023)

Comparative combustion, emission, and performance analysis of a diesel engine using carbon nanotube (CNT) blended with three different generations of biodiesel - Aman Singh Rajpoot; Gaurav Saini; Hussain Mohamed Chelladurai; Anoop Kumar Shukla; Tushar Choudhary (Environmental Science and Pollution Research, 2023)

Spatial distribution and characteristics of microplastics and associated contaminants from mid-altitude lake in NW Himalaya - Mehta Bulbul; Sunil Kumar; Kumar Ajay; Ambili Anoop (Chemosphere, 2023)

Pattern and drivers of danaine butterfly migration in Southern India: implications for conservation - P. A. Vinayan; M. A. Yathumon; N. S. Sujin; B. N. Anjan Kumar; P. A. Ajayan; P. K. Muneer; N. M. Vishnu; C. S. Anwar; N. R. Anoop (Journal of Insect Conservation, 2023)

Genome-Wide Identification of Histone Modification (HM) Gene Family and Their Expression Patterns Under Abiotic Stress and Different Developmental Stages of Tea (Camellia assamica) - Sangeeta Borchetia; Madhurjya Gogoi; Hukam C. Rawal; Pradeep Kumar Patel; Monika Chakraborty; Hemanta Saikia; Jyoti Nishad; Victor J. Ilango; Anoop Kumar Barooah; Tapan Kumar Mondal (Journal of Plant Growth Regulation, 2023)

Distribution of organochlorine pesticides in surface and deep waters of the Southern Indian Ocean and coastal Antarctic waters - Krushna Vudamala; Paromita Chakraborty; Ramesh Chatragadda; Anoop Kumar Tiwari; Asif Qureshi (Environmental Pollution, 2023)

Alley Cropping System in Degraded Land of Central India: Evaluation of Crop Performance, Economic Benefit and Soil Nutrients Availability - Sunil Kumar; T. Kiran Kumar; Mahendra Prasad; J. B. Singh; Mukesh Choudhary; Anoop Kumar Dixit; Probir Kumar Ghosh (International Journal of Plant Production, 2023)

Microplastics in multimedia environment: A systematic review on its fate, transport, quantification, health risk, and remedial measures - Pawan Kumar Rose; Monika Jain; Navish Kataria; Prafulla Kumar Sahoo; Vinod Kumar Garg; Anoop Yadav (Groundwater for Sustainable Development, 2023)

Identification and characterization of a fertility restorer line in Bhut Jolokia - Vivek Kumar Singh; Anoop Anand Malik; Md Aminul Islam; Shyam Sundar Sharma; Shashi Bhushan Tripathi (Vegetos, 2023)

Laminating STRATH block chain technology- SWOT architectures to endure business strategy between digital transformation, firms and supply chains capabilities for sustainability - Atul Kumar Sahu; Nitin Kumar Sahu; Anoop Kumar Sahu (Journal of Cleaner Production, 2023)

Treatment of textile industry wastewater by using high-performance forward osmosis membrane tailored with alpha-manganese dioxide nanoparticles for fertigation - Harshita Jain; Ajay Kumar; Anoop Kumar Verma; Shikha Wadhwa; Vishnu D. Rajput; Tatiana Minkina; Manoj Chandra Garg (Environmental Science and Pollution Research, 2022)

Identification of vaccine candidate against Omicron variant of SARS-CoV-2 using immunoinformatic approaches - Aasim; Ruchika Sharma; C. R. Patil; Anoop Kumar; Kalicharan Sharma (In Silico Pharmacology, 2022)

CO2 gas sensing properties of Na3BiO4-Bi2O3 mixed oxide nanostructures - Sandeep Gupta; Anoop Mampazhasseri Divakaran; Kamlendra Awasthi; Manoj Kumar (Environmental Science and Pollution Research, 2022)

Evaluating the efficacy of stool sample on Xpert MTB/RIF Ultra and its comparison with other sample types by meta-analysis for TB diagnostics - Vishal Sharma; Anoop Singh; Mohita Gaur; Deepti Rawat; Anjali Yadav; Rajan; Chanchal Kumar; Mandira Varma-Basil; Sheelu Lohiya; Vishal Khanna; Ashwani Khanna; Anil Chaudhry; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

Correction: The effects on performance and emission characteristics of DI engine fuelled with CeO2 nanoparticles addition in diesel/tyre pyrolysis oil blends - Upendra Rajak; Prerana Nashine; Prem Kumar Chaurasiya; Tikendra Nath Verma; Abhishek Dasore; Kamal Kishore Pathak; Gaurav Dwivedi; Anoop Kumar Shukla; Gaurav Saini (Environment, Development and Sustainability, 2022)

Heavy metal impression in surface sediments and factors governing the fate of macrobenthic communties in tropical estuarine ecosystem, India - Muralidharan Ratheesh Kumar; Krishnan Anoop Krishnan; Varghese Vimexen; Abdul Kareem Faisal; Mohan Mohind; Vijayan Arun (Environmental Science and Pollution Research, 2022)

Land use land cover changes on Asia’s largest freshwater lake and their impact on society and environment - Mohammad Suhail Meer; Anoop Kumar Mishra; Kattukota Nagamani (Arabian Journal of Geosciences, 2022)

The effects on performance and emission characteristics of DI engine fuelled with CeO2 nanoparticles addition in diesel/tyre pyrolysis oil blends - Upendra Rajak; Prerana Nashine; Prem Kumar Chaurasiya; Tikendra Nath Verma; Abhishek Dasore; Kamal Kishore Pathak; Gauav Dwivedi; Anoop Kumar Shukla; Gaurav Saini (Environment, Development and Sustainability, 2022)

Assessment of the impact of flood on groundwater hydrochemistry and its suitability for drinking and irrigation in the River Periyar Lower Basin, India - Appukuttanpillai Krishnakumar; Jeenu Jose; Seenipandi Kaliraj; Sanal Kumar Aditya; Krishnan Anoop Krishnan (Environmental Science and Pollution Research, 2022)

Abscisic acid and aloe-emodin against NS2B-NS3A protease of Japanese encephalitis virus - SaiPriyanka Bhimaneni; Anoop Kumar (Environmental Science and Pollution Research, 2022)

Impact analysis of biodiesel production parameters for different catalyst - Gaurav Dwivedi; Siddharth Jain; Anoop Kumar Shukla; Puneet Verma; Tikendra Nath Verma; Gaurav Saini (Environment, Development and Sustainability, 2022)

Heavy metals in hair and nails as markers of occupational hazard among welders working in United Arab Emirates - Hisaa Nassir Abdulla Lotah; Anoop Kumar Agarwal; Razia Khanam (Toxicological Research, 2022)

Composition and distribution pattern of plankton communities in lagoon and offshore region of Kavaratti Atoll, Lakshadweep Archipelago, India - Sibin Antony; Vinu V. Dev; M. Ratheesh Kumar; K. Anoop Krishnan (Sustainable Water Resources Management, 2021)

Development of titanium dioxide incorporated ultrathin cellulose acetate membrane for enhanced forward osmosis performance - Harshita Jain; Renu Dhupper; Anoop Kumar Verma; Manoj Chandra Garg (Nanotechnology for Environmental Engineering, 2021)

Observing a severe flooding over southern part of India in monsoon season of 2019 - Anoop Kumar Mishra (Journal of Earth System Science, 2021)

A Comprehensive in Silico Analysis for Identification of Immunotherapeutic Epitopes of HPV-18 - Bharti Gupta; Anoop Kumar; Parikipandla Sridevi (International Journal of Peptide Research and Therapeutics, 2021)

Synthesis of styryl-linked fused dihydropyridines by catalyst-free multicomponent reactions - Rahul Yadav; Tasneem Parvin; Anoop Kumar Panday; Lokman H. Choudhury (Molecular Diversity, 2021)

Grazing behaviour of tropical calanoid copepods and its effect on phytoplankton community structure - M Ratheesh Kumar; K Anoop Krishnan (Environmental Monitoring and Assessment, 2021)

Physical/chemical weathering and climate fluctuations during last ~6000 years—investigation through a sediment core, off Mahanadi River mouth, western Bay of Bengal - Janhavi Kangane; Ganapati N. Nayak; Anoop Kumar Tiwari; Maheshwar R. Nasnodkar (Arabian Journal of Geosciences, 2021)

Remote sensing of extreme flash floods over two southern states of India during North-East monsoon season of 2020 - Anoop Kumar Mishra; Vanganuru Nagaraju (Natural Hazards, 2021)

Bioaccumulation of metals by edible bivalve Saccostrea cucullata and its application as a bioindicator of metal pollution, tropical (Zuari) estuary, Goa, India - Racheal J. Rodrigues; Maheshwar R. Nasnodkar; Ganapati N. Nayak; Anoop Kumar Tiwari (Arabian Journal of Geosciences, 2021)

Metals toxicity and its correlation with the gene expression in Alzheimer's disease - Jyoti Yadav; Anoop Kumar Verma; Md. Kaleem Ahmad; Ravindra K. Garg; Shiuli; Abbas Ali Mahdi; Shrikant Srivastava (Molecular Biology Reports, 2021)

Spring-neap tides influence on bioavailability of metals and bioaccumulation in edible biota of the Zuari (tropical) Estuary - Maheshwar R. Nasnodkar; Ganapati N. Nayak; Priyanka P. Bhangle; Anoop Kumar Tiwari (Environmental Monitoring and Assessment, 2021)

Scyphozoan jellyfish blooms and their relationship with environmental factors along the South-eastern Arabian Sea - Abdul Riyas; Neelesh Dahanukar; Krishnan Anoop Krishnan; Appukuttannair Biju Kumar (Marine Biology Research, 2021)

Prevalence of human papillomavirus 16 genotype in Anuppur district, Madhya Pradesh - Bharti Gupta; Lokeswara Balakrishna Sunnam; Anoop Kumar; Sridevi Parikipandla (Molecular Biology Reports, 2021)

Observational study of a severe snowfall avalanche over a state in North India in November 2019 using GIS - Mohammad Suhail Meer; Anoop Kumar Mishra (Journal of Earth System Science, 2020)

Chemical carcinogen safety testing: OECD expert group international consensus on the development of an integrated approach for the testing and assessment of chemical non-genotoxic carcinogens - Miriam N. Jacobs; Annamaria Colacci; Raffaella Corvi; Monica Vaccari; M. Cecilia Aguila; Marco Corvaro; Nathalie Delrue; Daniel Desaulniers; Norman Ertych; Abigail Jacobs; Mirjam Luijten; Federica Madia; et al. (Archives of Toxicology, 2020)
While regulatory requirements for carcinogenicity testing of chemicals vary according to product sector and regulatory jurisdiction, the standard approach starts with a battery of genotoxicity tests (which include mutagenicity assays). If any of the in vivo genotoxicity tests are positive, a lifetime rodent cancer bioassay may be requested, but under most chemical regulations (except plant protection, biocides, pharmaceuticals), this is rare. The decision to conduct further testing based on genotoxicity test outcomes creates a regulatory gap for the identification of non-genotoxic carcinogens (NGTxC). With the objective of addressing this gap, in 2016, the Organization of Economic Cooperation and Development (OECD) established an expert group to develop an integrated approach to the testing and assessment (IATA) of NGTxC. Through that work, a definition of NGTxC in a regulatory context was agreed. Using the adverse outcome pathway (AOP) concept, various cancer models were developed, and overarching mechanisms and modes of action were identified. After further refining and structuring with respect to the common hallmarks of cancer and knowing that NGTxC act through a large variety of specific mechanisms, with cell proliferation commonly being a unifying element, it became evident that a panel of tests covering multiple biological traits will be needed to populate the IATA. Consequently, in addition to literature and database investigation, the OECD opened a call for relevant assays in 2018 to receive suggestions. Here, we report on the definition of NGTxC, on the development of the overarching NGTxC IATA, and on the development of ranking parameters to evaluate the assays. Ultimately the intent is to select the best scoring assays for integration in an NGTxC IATA to better identify carcinogens and reduce public health hazards.

Zinc and phosphate solubilizing Rhizobium radiobacter (LB2) for enhancing quality and yield of loose leaf lettuce in saline soil - Maya Verma; Anoop Singh; Deepa H. Dwivedi; Naveen Kumar Arora (Environmental Sustainability, 2020)

Remote Sensing Application for Exploring Changes in Land-Use and Land-Cover Over a District in Northern India - Mohammad Suhail Meer; Anoop Kumar Mishra (Journal of the Indian Society of Remote Sensing, 2020)

On the generation and propagation of Makran swells in the Arabian Sea - Thondithala R. Anoop; Puthuveetil R. Shanas; Valliyil M. Aboobacker; V. Sanil Kumar; Leela Sheela Nair; Ravindran Prasad; Srinivas Reji (International Journal of Climatology, 2020)
Persistent and periodic northerly low‐level jets have been identified in the South Asian mid‐latitudes and subtropics, which are modified by the presence of Makran mountain ranges adjacent to the central south coast of Pakistan, where they blow predominantly in the west‐northwest to northeast directions. These winds lead to the generation of a new wave system and propagate through the Arabian Sea as “makran swells”. They are prevalent during October to May. The measurements along the west coast of India reveal systematic variations in the wave spectra relating the makran events. This has been further verified through the WaveWatch III simulations forced by the CFSR winds. The significant wave heights up to 4.5 m were hindcasted in the northern Arabian Sea during these events. Once generated, the makran swells propagate to the eastern Arabian Sea and western Arabian Sea with directional sectors of 300–360° and 0–60°, respectively. The characteristic features and the spatial extension of the makran swells are particularly analysed.

Satellite-based monitoring of recent heavy flooding over north-eastern states of India in July 2019 - Anoop Kumar Mishra; Mohammad Suhail Meer; Vanganuru Nagaraju (Natural Hazards, 2019)

Examining climate change impact on the variability of ground water level: A case study of Ahmednagar district, India - N A Sivarajan; Anoop Kumar Mishra; Mohammd Rafiq; V Nagraju; Sagarika Chandra (Journal of Earth System Science, 2019)

Space-based monitoring of severe flooding of a southern state in India during south-west monsoon season of 2018 - Anoop Kumar Mishra; Vanganuru Nagaraju (Natural Hazards, 2019)

On remote sensing of convective clouds over Indian continent and quantification of their variability in a warming environment - Anoop Kumar Mishra (International Journal of Remote Sensing, 2019)

Biomass Energy for Economic and Environmental Sustainability in India - Narendra Mohan; Anoop Kumar Kanaujia (Sugar Tech, 2019)

Modelling Chorabari Lake outburst flood, Kedarnath, India - Mohammd Rafiq; Shakil Ahmad Romshoo; Anoop Kumar Mishra; Faizan Jalal (Journal of Mountain Science, 2019)

Sediment composition and its effect on the productivity in Larsemann Hills, East Antarctica - Shabnam Choudhary; Ganapati Nayak; Anoop Kumar Tiwari; Neloy Khare (Arabian Journal of Geosciences, 2018)

The complete mitochondrial genome of Euphlyctis karaavali (Amphibia: Anura) with a note on its range expansion - V. S. Anoop; Kiran S. Kumar; K. C. Sivakumar; Dinesh Reghunathan; P. Manoj; Kaushik Deuti; Sanil George (Conservation Genetics Resources, 2017)

Effect of protection against hot climate on growth performance, physiological response and endocrine profile of growing lambs under semi-arid tropical environment - Kalyan De; Davendra Kumar; Anoop Kumar Singh; Kamal Kumar; Artabandhu Sahoo; Syed Mohammed Khursheed Naqvi (Tropical Animal Health and Production, 2017)

Rapid visual screening of different housing typologies in Himachal Pradesh, India - Sreerama Ajay Kumar; Chenna Rajaram; Shashank Mishra; Ramancharla Pradeep Kumar; Anoop Karnath (Natural Hazards, 2017)

Development of multifunctional heterocyclic Schiff base as a potential metal chelator: a comprehensive spectroscopic approach towards drug discovery - Manojkumar Jadhao; Chayan Das; Anoop Rawat; Himank Kumar; Ritika Joshi; Sudipta Maiti; Sujit Kumar Ghosh (JBIC Journal of Biological Inorganic Chemistry, 2017)

Changes in DNA methylation levels during seed development in Jatropha curcas - PRATIMA PANDEY; ANOOP ANAND MALIK; KAMLESH KUMAR; MADAN SINGH NEGI; SHASHI BHUSHAN TRIPATHI (Journal of Genetics, 2016)

Monitoring Tamil Nadu flood of 2015 using satellite remote sensing - Anoop Kumar Mishra (Natural Hazards, 2016)

Seed traits, fatty acid profile and genetic diversity assessment in Pongamia pinnata (L.) Pierre germplasm - Shyam Sundar Sharma; Md Aminul Islam; Anoop Anand Malik; Kamlesh Kumar; Madan Singh Negi; Shashi Bhushan Tripathi (Physiology and Molecular Biology of Plants, 2016)

Indian Ocean Dipole modulated wave climate of eastern Arabian Sea - T. R. Anoop; V. Sanil Kumar; P. R. Shanas; J. Glejin; M. M. Amrutha (Ocean Science, 2016)
Intrinsic modes of variability have a significant role in driving the climatic oscillations in the oceanic processes. In this paper, we investigate the influence of an inter-annual mode of variability, the Indian Ocean Dipole (IOD), on the wave climate of the eastern Arabian Sea (AS). Using measured, modeled and reanalysis wave data and reanalysis wind data, we show that the IOD plays a major role in the variability of wave climate of the study region. Due to the IOD-induced changes in equatorial sea surface temperature and sea level pressure, the winds from the northern AS gets modified and cause inter-annual variability in the wave climate over the eastern AS. The changes in wind field over the AS due to the IOD influence the generation or dissipation of the wave field and hence cause a decrease in northwest short-period waves during positive IOD and an increase during negative IOD.

Spatial and temporal variations of wave height in shelf seas around India - V. Sanil Kumar; T. R. Anoop (Natural Hazards, 2015)

A study on the occurrence of flood events over Jammu and Kashmir during September 2014 using satellite remote sensing - Anoop Kumar Mishra (Natural Hazards, 2015)

An insight into deltamethrin induced apoptotic calcium, p53 and oxidative stress signalling pathways - Anoop Kumar; Dinakar Sasmal; Neelima Sharma (Toxicology and Environmental Health Sciences, 2015)

A study on reflection pattern of swells from the shoreline of peninsular India - T. R. Anoop; V. Sanil Kumar; Johnson Glejin (Natural Hazards, 2014)

Estimation of heavy rainfall during cyclonic storms from microwave observations using nonlinear approach over Indian Ocean - Anoop Kumar Mishra (Natural Hazards, 2012)

The study of microclimate in response to different plant community association in tropical moist deciduous forest from northern India - Soumit K. Behera; Ashish K. Mishra; Nayan Sahu; Amrit Kumar; Niraj Singh; Anoop Kumar; Omesh Bajpai; L. B. Chaudhary; Prem B. Khare; Rakesh Tuli (Biodiversity and Conservation, 2012)

Rainfall Estimation from Combined Observations Using KALPANA-IR and TRMM- Precipitation Radar Measurements over Indian Region - Anoop Kumar Mishra; Rakesh M. Gairola; Vijay K. Agarwal (Journal of the Indian Society of Remote Sensing, 2012)

Removal of Atrazine from Water by Low Cost Adsorbents Derived from Agricultural and Industrial Wastes - Rajendra Kumar Sharma; Anoop Kumar; P. E. Joseph (Bulletin of Environmental Contamination and Toxicology, 2008)

Persistence and vertical distribution of termiticide fipronil in modified ground board test - KK Sharma; Kalpana; Vandana Sharma; Pratigya Gupta; Maisnam Jaya; Anoop Kumar; Bijendra Singh (Environmental Monitoring and Assessment, 2008)

Persistence and Dissipation Kinetics of Spiromesifen in Chili and Cotton - K. K. Sharma; Cherukuri Sreenivasa Rao; J. K. Dubey; S. K. Patyal; N. S. Parihar; R. S. Battu; Vandana Sharma; Pratigya Gupta; Anoop Kumar; Kalpana; Maisnam Jaya; Balwinder Singh; et al. (Environmental Monitoring and Assessment, 2007)

High glucose-induced membrane translocation of PKC βI is associated with Arf6 in glomerular mesangial cells - Anoop Kumar Padival; Karen S. Hawkins; Chunfa Huang (Molecular and Cellular Biochemistry, 2004)